2001
DOI: 10.1118/1.1354998
|View full text |Cite
|
Sign up to set email alerts
|

Tissue mimicking materials for a multi‐imaging modality prostate phantom

Abstract: Materials that simultaneously mimic soft tissue in vivo for magnetic resonance imaging ͑MRI͒, ultrasound ͑US͒, and computed tomography ͑CT͒ for use in a prostate phantom have been developed. Prostate and muscle mimicking materials contain water, agarose, lipid particles, protein, Cu ϩϩ , EDTA, glass beads, and thimerosal ͑preservative͒. Fat was mimicked with safflower oil suffusing a random mesh ͑network͒ of polyurethane. Phantom material properties were measured at 22°C. ͑22°C is a typical room temperature at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 23 publications
(28 reference statements)
1
57
0
2
Order By: Relevance
“…TM materials were made of several chemicals for the following reasons 7,11,12 : Milk has the same properties as human tissue; Thimerosal prevents bacterial invasion in milk; Mesh filters remove any impurities that may have been introduced during the prior concentrating and commercial packaging of milk; Agarose is a bonding material and MR T2 relaxation time modifier; Deionized water doesn't include metal ions which lower the relaxation times unlike tap water; Propanol increases the speed of sound for water (1,484 m/sec) to that for soft tissues (1,540 m/sec); BaSO 4 is for CT contrast enhancement; Cu 2+ /EDTA decreases MR T1 relaxation time; Glass beads are for US contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TM materials were made of several chemicals for the following reasons 7,11,12 : Milk has the same properties as human tissue; Thimerosal prevents bacterial invasion in milk; Mesh filters remove any impurities that may have been introduced during the prior concentrating and commercial packaging of milk; Agarose is a bonding material and MR T2 relaxation time modifier; Deionized water doesn't include metal ions which lower the relaxation times unlike tap water; Propanol increases the speed of sound for water (1,484 m/sec) to that for soft tissues (1,540 m/sec); BaSO 4 is for CT contrast enhancement; Cu 2+ /EDTA decreases MR T1 relaxation time; Glass beads are for US contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for preparing the TM materials are modified from those developed in Dr. Ernest L. Madsen's laboratory at the University of Wisconsin Madison and more details are in Lee et al 8,11 .…”
Section: Tm Materials Preparationmentioning
confidence: 99%
“…More details can be referred in [15]. The phantom, which has the similar electromagnetic parameters with tumor, is a good choice for thermo-acoustic imaging experiment [21] to test the imaging ability of the MITAT system. Pictures of the phantom and the achieved thermo-acoustic image are shown in Fig.…”
Section: Digital Thermo-acoustic Signal Processingmentioning
confidence: 99%
“…[26][27][28][29] TMM phantoms bridge the gap in translational research without the need of direct experimentation on humans or animals. The phantoms designed with TMMS are essential for assessing different technologies, and for training and research.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] The key parameters in material characterization for ultrasound imaging include the acoustic velocity, the acoustic impedance, and the acoustical attenuation, while Young's modulus is an important parameter for elastography phantoms. Madsen et al 30 have demonstrated the use of TM phantoms for standardization of both ultrasound imaging of the prostate 26 and for elastographic imaging 18, 31 using agar and gelatine materials. Anderson et al 32 have also shown the effect of graphite concentration on shear wave speed in gelatine based phantoms.…”
Section: Introductionmentioning
confidence: 99%